A note on the unemployment volatility puzzle. (28th April 2022) - Kokonas, Nikolaos
Abstract: This paper features an economy with frictional labour markets, Nash bargaining, cyclical opportunity cost of employment and demand-determined output. I show that the model generates big responses of unemployment to productivity movements. The key insight is that strongly countercyclical markups amplify the impact of aggregate shocks on the fundamental surplus, and as a consequence, on labour market outcomes. This answers the critique of Chodorow-Reich and Karabarbounis that the cyclicality of the opportunity cost poses a challenge to the solution of the unemployment volatility puzzle.